IKAROS—how many feathers have you lost: mild and severe phenotypes in IKZF1 deficiency - Strauss, Timmy; Körholz, Julia; Kuehn, Hye Sun; Gil Silva, Agustin A.; Taube, Franziska; Trautmann-Grill, Karolin; Stittrich, Anna; Pietzsch, Leonora; Wiedemuth, Ralf; Wahn, Volker; von Bernuth, Horst; Rosenzweig, Sergio D.; et al. (Frontiers in Pediatrics, 2024)
Heterozygous germline variants in human IKZF1 encoding for IKAROS define an inborn error of immunity with immunodeficiency, immune dysregulation and risk of malignancy with a broad phenotypic spectrum. Growing evidence of underlying pathophysiological genotype-phenotype correlations helps to improve our understanding of IKAROS-associated diseases. We describe 6 patients from 4 kindreds with two novel IKZF1 variants leading to haploinsufficiency from 3 centers in Germany. We also provide an overview of first symptoms to a final diagnosis including data from the literature.